2021
DOI: 10.1002/jcla.24155
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the microbial spectrum and antibiotic sensitivity of uropathogens isolated from patients with urinary stones

Abstract: Purpose The characteristics and resistance patterns of urine bacteriology urolithiasis patients between male and female have not been extensively studied. This study aims to investigate the gender differences in microbial spectrum and antibiotic susceptibility of uropathogens isolated from urolithiasis patients and provide insights for appropriate antimicrobial therapies. Materials and Methods We retrospectively collected clinical microbiology data from urine culture in urolithiasis patients between March 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…In our study, multivariate analysis revealed that male gender, <19 months, weight < 11:5 (kg), height < 83 (cm), BMI < 17:09, BUN > 4:08 (mmol/L), and internal drainage were risk factors of postoperative UTI in pediatric UPJO patients, suggesting that younger boys with lower weight or height, lower BMI, higher BUN, or internal drainage may require more attention regarding postoperative UTI. A previous study demonstrated that uropathogens isolated from male urolithiasis patients were more resistant to antimicrobials than female, revealing the presence of sex differences with regard to microbial spectrum and antibiotic sensitivity [18]. Consistent with our study, gender difference was also observed in patients with UTI after retrograde upper urinary lithotripsy [19].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, multivariate analysis revealed that male gender, <19 months, weight < 11:5 (kg), height < 83 (cm), BMI < 17:09, BUN > 4:08 (mmol/L), and internal drainage were risk factors of postoperative UTI in pediatric UPJO patients, suggesting that younger boys with lower weight or height, lower BMI, higher BUN, or internal drainage may require more attention regarding postoperative UTI. A previous study demonstrated that uropathogens isolated from male urolithiasis patients were more resistant to antimicrobials than female, revealing the presence of sex differences with regard to microbial spectrum and antibiotic sensitivity [18]. Consistent with our study, gender difference was also observed in patients with UTI after retrograde upper urinary lithotripsy [19].…”
Section: Discussionsupporting
confidence: 91%
“…Higher rates of urinary tract infections with Escherichia coli, Staphylococcus aureus, Enterobacter, and Klebsiella Pneumonia were detected among females compared to males, while only Escherichia coli and Staphylococcus aureus were more prevalent among urinary stones female patients in another study [43].…”
Section: Discussionmentioning
confidence: 79%
“…The relation between gender and antibiotic resistance was also noted in other studies. For example, higher susceptibility rates of Escherichia coli isolates to piperacillin-tazobactam, and imipenem were also associated with female gender, while nitrofurantoin susceptibility was not associated with gender [44]. On the other hand, in Bangladesh, Escherichia coli strains in male patients were more resistant to amikacin, colistin, and nitrofurantoin [45].…”
Section: Discussionmentioning
confidence: 97%
“…Higher rates of urinary tract infections with Escherichia coli, Staphylococcus aureus, Enterobacter, and Klebsiella Pneumonia were detected among females compared to males, while only Escherichia coli and Staphylococcus aureus were more prevalent among urinary stones female patients in another study [43]. Urine isolates in males were more resistant to imipenem, nitrofurantoin, amoxicillin-clavulanic, piperacillin-tazobactam, and cefaclor.…”
Section: Discussionmentioning
confidence: 85%